Cytoprotective Effects of Cell-Permeable Bifunctional Antioxidant Enzyme, GST-TAT-SOD, against Cisplatin-Induced Cell Damage. (30th November 2017) - Pan, Jianru; Li, Lingling; Liang, Lili; He, Huocong; Su, Ying; Wang, Xiangling; Liu, Shutao
Abstract : GST-TAT-SOD, a cell-permeable bifunctional antioxidant enzyme, is a potential selective radioprotector. This study aimed to investigate the cytoprotective activity of GST-TAT-SOD against cisplatin-induced damage. The current study showed that cisplatin induced the formation of reactive oxygen species in normal L-02 cells. GST-TAT-SOD (2000 U/mL) executed its antioxidant role by directly scavenging excess intracellular free radicals and augmenting cellular antioxidant defense such as reducing MDA level, enhancing the SOD activity, GST activity, and T-AOC. Thus, it suppressed the growth inhibition and apoptosis of cisplatin-treated normal cells. Meanwhile, the growth inhibition of tumor cells (SMMC-7721) caused by cisplatin was unaffected by GST-TAT-SOD pretreatment. GST-SOD, as a comparison, seemed to be powerless for related indicators as it could not enter into cells without cell-permeating peptide. These results suggest that GST-TAT-SOD might be a potential cytoprotective agent for cisplatin-induced side effects.